Trans-3, 4-Disubstituted pyrrolidines as inhibitors of the human aspartyl protease renin. Part II: Prime site exploration using an oxygen linker. Issue 8 (15th April 2015) - Sellner, Holger; Cottens, Sylvain; Cumin, Frédéric; Ehrhardt, Claus; Kosaka, Takatoshi; Lorthiois, Edwige; Ostermann, Nils; Webb, Randy L.; Rigel, Dean F.; Wagner, Trixie; Maibaum, Jürgen
Graphical abstract